The Effect of Organizational Climate and Compensation on Turnover Intention - Watoni, M. Hibbul (Winter Journal: IMWI Student Research Journal, 2023)
The role of the global banking sector in a country's economy is very important. All fields related to finance definitely need banking services. Banking products and services in Sukoharjo are expected to improve the economic welfare of the area. This study aims to understand the effect of organizational climate and compensation on capital turnover intentions in banks in the Sukoharjo area. This research included quantitative research with sampling techniques using the simple random sampling method. The sample size used was 92 respondents. Data collection techniques using questionnaires and statistical analysis with structural equation modeling (SEM) using SMART-PLS4 software, The results of this study show that organizational climate and compensation negatively affect turnover intention.